Digital analysis of vaults in English Medieval architecture - Buchanan, Alexandrina, author.
1 online resource
Keywords: "Medieval churches are one of the most remarkable creative and technical achievements in architectural history. The complex vaults spanning their vast interiors have fascinated both visitors and worshippers alike for over 900 years, prompting many to ask: 'How did they do that?' Yet very few original texts or drawings survive to explain the processes behind their design or construction. This book presents a ground-breaking new approach for analysing medieval vaulting using advanced digital technologies. Focusing on the intricately patterned rib vaulting of 13th and 14th century England, the authors re-examine a series of key sites within the history of Romanesque and Gothic Architecture, using extensive digital surveys to examine the geometries of the vaults and provide new insights into the design and construction practices of medieval masons. From the simple surfaces of 11th-century groin vaults to the gravity-defying pendant vaults of the 16th century, they explore a wide range of questions including: How were medieval vaults conceived and constructed? How were ideas transferred between sites? What factors led to innovations? How can digital methods be used to enhance our understanding of medieval architectural design? Featuring over 150 high quality illustrations that bring the material and the methods used to life, Digital Analysis of Vaults in English Medieval Architecture is ideal reading for students, researchers and anyone with an interest in medieval architecture, construction history, architectural history and design, medieval geometry and digital heritage"--